2019
DOI: 10.3390/coatings9120858
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Heat Treatment Temperatures on the Microstructure, Corrosion, and Mechanical Properties Behavior of Fe-Based Amorphous/Nanocrystalline Coatings

Abstract: Fe-based amorphous/nanocrystalline coatings with smooth, compact interior structure and low porosity were fabricated via supersonic plasma spraying (SPS). The coatings showed outstanding corrosion resistance in a 3.5% NaCl solution at room temperature. In order to analyze the effect of annealing treatment on the microstructure, corrosion resistance and microhardness, the as-sprayed coating was annealed for 1 h under different temperatures such as 350, 450, 550 and 650 °C, respectively. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The corrosion behaviour for Fe-based MG composite coatings in different environments was primarily influenced by composition, amorphicity level and defective regions (porosity, inter-splat) [66,124,128,137,141,231,374]. In recent years, the corrosion properties of in-situ Febased MG composite coatings have been widely investigated [121,133,138,142,161,169,265,277,298,[375][376][377][378][379][380][381][382][383][384][385][386][387]. For instance, Lin et al [121] observed that porosities, inter-splats and oxides had deleterious effect on the corrosion behaviour of arc-sprayed FeNiCrB-SiNbW MG composite coating.…”
Section: In-situ Composite Coatingsmentioning
confidence: 99%
“…The corrosion behaviour for Fe-based MG composite coatings in different environments was primarily influenced by composition, amorphicity level and defective regions (porosity, inter-splat) [66,124,128,137,141,231,374]. In recent years, the corrosion properties of in-situ Febased MG composite coatings have been widely investigated [121,133,138,142,161,169,265,277,298,[375][376][377][378][379][380][381][382][383][384][385][386][387]. For instance, Lin et al [121] observed that porosities, inter-splats and oxides had deleterious effect on the corrosion behaviour of arc-sprayed FeNiCrB-SiNbW MG composite coating.…”
Section: In-situ Composite Coatingsmentioning
confidence: 99%
“…Oxygen enters the coating to form oxides that reduce porosity, which is the main factor improving corrosion resistance [26,29]. However the number of oxides in the coatings presented an obvious increase with increasing temperature, and the corrosion resistance of the coatings showed an obvious reduction [25]. The formation of new oxides is suppressed during vacuum heat treatment.…”
Section: Micromorphology Of the Coating Surfacementioning
confidence: 99%
“…A decrease in coating volume is the main reason for the re-formation of pores and cracks within (in Figure 3e). Liu's research [25] shows that the number of cracks in coatings obviously increases when the temperature of atmospheric heat treatment is increased from 350 • C to 650 • C. In this study, the phenomenon of increased cracks in the coating occurred when the heating temperature reached 1050 • C. Different from the cracking mechanism of the expansion of coating volume caused by the formation of oxides in atmospheric heat treatment, the cracking of the coating in vacuum heat treatment is caused by the different expansion coefficients of Al 2 O 3 and TiO 2 [30].…”
Section: Interface Bonding Between Coating and Substratementioning
confidence: 99%
See 1 more Smart Citation
“…The XRD pattern of the optimized S7coating (coded by C coating in the mentioned reference) indicated no new phase or deviation (compared to that of milled powder) appeared in the coating, indicating no solid solution formed during spraying. Coating peaks are broader than milled powder peaks due to the amorphism and grain size reduction of the coating resulting from rapid solidification of melted granulates during spraying [45]. The grain size of the Cr2O3 in the S7 coating was calculated to be 54 nm using the Williamson-Hall method through data of (012), ( 104), (110), and (116) reflections [44].…”
Section: Nm 100 Nmmentioning
confidence: 99%